2017
DOI: 10.1097/mpa.0000000000000818
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Experience of Diagnosis, Management, and Burden of Neuroendocrine Tumors

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 16 publications
5
51
0
Order By: Relevance
“…Delay in diagnosis is a particular issue in rare diseases because it results in delayed treatment, increased morbidity, and potentially life-threatening complications. 10,11 The cycling of patients through multiple providers and sometimes extensive and repetitive testing and the possibility of conflicting recommendations for treatment may worsen symptoms and increase the psychological and emotional burden for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Delay in diagnosis is a particular issue in rare diseases because it results in delayed treatment, increased morbidity, and potentially life-threatening complications. 10,11 The cycling of patients through multiple providers and sometimes extensive and repetitive testing and the possibility of conflicting recommendations for treatment may worsen symptoms and increase the psychological and emotional burden for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gastroenteropancreatic neuroendocrine tumor (GEP‐NET) is a relatively rare and heterogeneous group of neoplasms . Advanced disease cannot be cured and it is a lethal condition associated with impaired quality of life . Disease stage as well as tumor location and grade provide prognostic information and are major determinants in the therapeutic algorithm .…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are limited data on patients' unmet needs regarding the provision of NET information at diagnosis. A survey of 758 patients in the United States reported that 57% found answers to their NET‐related questions, yet only 45% were given sufficient information after diagnosis and 58% would have liked better direction in obtaining information . Other surveys also found that patients struggle to source relevant information .…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 758 patients in the United States reported that 57% found answers to their NET-related questions, yet only 45% were given sufficient information after diagnosis and 58% would have liked better direction in obtaining information. 14 Other surveys also found that patients struggle to source relevant information. 15,16 This finding is reflected in our survey where many patients reported using the internet and patient associations to obtain information on NETs.…”
Section: Discussionmentioning
confidence: 99%